Molecular Docking Study of Chalcone Derivatives as Potential Inhibitors of SARS-CoV-2 Main Protease - Fitriana, Adita Silvia; Royani, Sri (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
SARS-CoV-2 main protease is a potential target for the development of AntiCOVID-19. Several chalcones have inhibitory activity against 3CLpro SARS-CoV and 3CLpro MERS-CoV. This study aims to predict the potential of chalcones in inhibiting 3CLpro SARS-CoV-2, which plays a role in the viral replication process. In silico research carried the prediction through molecular docking toward proteins with PDB ID 6LU7 and 6Y2F. Compound K27 has a docking score more negative than lopinavir. This result indicates that compound K27 is predicted to inhibit the SARS-CoV-2 replication.